Examining consumer's intention to purchase sustainable building of residential property in Klang Valley, Malaysia - Woon, Siew Lim (2020)
The strict compliance for sustainable building projects is deemed necessary among building developers to gain competitive advantage. The goals of this research were five-fold: (a) to investigate the influence of attitude, subjective norm, perceived behavioral control, sustainability concerns, sustainability knowledge, government incentives, perceived quality and perceived value on consumers’ intention to purchase sustainable residential property buildings in the Klang Valley, Malaysia; (b) to examine the influence of sustainability concerns on consumers’ attitude towards purchasing sustainable buildings; (c) to assess the influence of sustainability concerns on subjective norm towards purchasing sustainable buildings; (d) to examine the influence of sustainability knowledge on subjective norm towards purchasing sustainable buildings; and (e) to determine the influence of government incentives on perceived behavioral control towards purchasing sustainable buildings. The extended theory of planned behavior was adopted in this study and 12 hypotheses were formulated. A self-administered questionnaire was employed for data collection using the systematic sampling method. 390 questionnaires were distributed to every fifth customer who walked into the selected sales galleries displaying sustainable buildings in the Klang Valley. The collected data was analyzed using the multiple regression analysis via the Statistical Package for Social Sciences (SPSS) version 26.0. The findings show attitude was the strongest predictor of purchase intention, followed by sustainability concerns and sustainability knowledge. Subjective norm, perceived behavioral control and government incentives were found to be equally important but no direct influence purchase intention. Lastly, perceived quality and perceived value did not influence purchase intention. The research findings can aid property marketers to have a better understanding of the factors that most significantly affect consumers’ intention to purchase sustainable residential property buildings in the Klang Valley, Malaysia.